Pembaharuan Hukum Pengelolaan Tanah Wakaf di Wilayah Pesisir Utara Jawa Tengah - Islamiyati, Islamiyati; Setyowati, Rofah; Rofiq, Ahmad (Jurnal Suara Hukum, 2023)
Abstract The legal renewal of waqf land management in the northern coastal area of Central Java is very important because there are legal problems with the practice of waqf land management. The research identified legal problems in the management of waqf land in the northern coastal area of Central Java and the solutions. The benefits of research as a novelty on waqf law enforcement and waqf land management so that waqf land can be managed optimally. This type of research is field research, using an empirical juridical approach, the data needed is primary and secondary data, the data is analyzed qualitatively and concluded inductively. The results of the study show that the legal problems of waqf land management in the northern coastal region of Central Java, namely; waqf practices occur orally; the community is not yet fully aware of the waqf laws set by the state and do not fully support the management of waqf land; there is an attitude of the heirs not supporting the heir as waqif; unprofessional nadzir resources; the nadzir's attitude in the management of waqf assets is not yet transparent and accountable; the legality of the validity of the nadzir has not yet been realized; and PPAIW has not carried out its duties optimally. The solution; carry out legal renewal of waqf land management by improving institutional aspects, juridical regulations, nadzir resources, support for facilities and infrastructure as well as government policies so that the objectives and benefits of waqf land can be felt by the community. Keywords: Legal renewal; management; waqf land; northern coastal area; Central Java.